Detection of hydrogen isotopes in Zircaloy-4 via femtosecond LIBS. Issue 6 (23rd April 2021) - Kautz, Elizabeth J.; Rönnebro, Ewa C. E.; Devaraj, Arun; Senor, David J.; Harilal, Sivanandan S.
Abstract : Spatio-temporal mapping of species in a femtosecond laser induced Zircaloy-4 plasma identified conditions well-suited for the detection and analysis of deuterium across a wide range of concentrations. Abstract : The analysis of hydrogen isotopes ( 1 H, 2 H, and 3 H) is crucial to several applications, including nuclear forensics and safeguards, characterization of nuclear fission and fusion reactor materials, geochemistry, and space exploration. Laser-induced breakdown spectroscopy (LIBS) is a promising tool for the real-time analysis of hydrogen isotopes. However, the accurate, quantitative analysis via LIBS can be challenging due to 1 H contamination on sample surfaces, residual 1 H in the analysis environment, minor amounts of solute 1 H, and spectral line broadening. Here, we characterize femtosecond laser induced plasmas from Zircaloy-4 targets with varying 1 H and 2 H concentrations in a He gas environment via spatially and temporally resolved optical emission spectroscopy. The impact of varying ambient gas pressure, the spatial distribution, and temporal histories of species viz., 1 Hα, 2 Hα, and Zr I on Zircaloy-4 plasma spectral features are reported. 1 Hα and Zr I emission features are found to have different ambient pressure dependencies and are separated in both space and time in the laser induced plasmas. Lastly, the measured 2 Hα emission intensities via femtosecond LIBS for a wide range of 2 H concentrations in Zircaloy-4 samples showed a linear trend when plotted versus known 2 H concentration.